2007
DOI: 10.1007/s10856-007-3310-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of amidated pectin based hydrogels for drug delivery system

Abstract: In the current studies attempts were made to prepare hydrogels by chemical modification of pectin with ethanolamine (EA) in different proportions. Chemically modified pectin products were crosslinked with glutaraldehyde reagent for preparing hydrogels. The hydrogels were characterized by Fourier transform infrared spectroscopy (FTIR), organic elemental analysis, X-ray diffraction studies (XRD), swelling studies, biocompatibility and hemocompatibility studies. Mechanical properties of the prepared hydrogels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 11 publications
4
45
0
Order By: Relevance
“…A strong amide I (-C=O) peak (1682cm -1 ) was observed on the SMM spectrum that contributed to the strong stretching vibrations of the amide I bond in MUC (peak 1636cm -1 ) and AZT, peak 1641cm -1 and 1670cm -1 (Patel et al, 2003;Tam et al, 2005). The ATR-FTIR spectra of SMMs, PEC, MUC, PEG and AZT depicted several peaks in the finger-print region (1450-650cm) which were consistent with what is reported in literature and expected for the AZT-loaded SMMs (Mishra et al, 2008;Patel et al 2003;Ravi et al, 2008). No apparent differences were observed between the FTIR spectra of drug-loaded and drug-free PEG-encl-PEC:MUC SMMs except for the presence of vibrational peaks corresponding to AZT in the former.…”
Section: Atr-ftir Analysis Of Components and The Azt-loaded Peg-encl-supporting
confidence: 89%
See 2 more Smart Citations
“…A strong amide I (-C=O) peak (1682cm -1 ) was observed on the SMM spectrum that contributed to the strong stretching vibrations of the amide I bond in MUC (peak 1636cm -1 ) and AZT, peak 1641cm -1 and 1670cm -1 (Patel et al, 2003;Tam et al, 2005). The ATR-FTIR spectra of SMMs, PEC, MUC, PEG and AZT depicted several peaks in the finger-print region (1450-650cm) which were consistent with what is reported in literature and expected for the AZT-loaded SMMs (Mishra et al, 2008;Patel et al 2003;Ravi et al, 2008). No apparent differences were observed between the FTIR spectra of drug-loaded and drug-free PEG-encl-PEC:MUC SMMs except for the presence of vibrational peaks corresponding to AZT in the former.…”
Section: Atr-ftir Analysis Of Components and The Azt-loaded Peg-encl-supporting
confidence: 89%
“…8 shows that the crystallinity of AZT-loaded PEG-encl-PEC:MUC SMMs was a result of the contribution by the highly crystalline AZT. The peaks observed in the diffractogram of AZT-loaded PEG-encl-PEC:MUC SMMs were sharp as those observed for AZT but were shifted slightly to the left by less than 1º and peak intensities were lower than those of observed for AZT which was probably because of the formation of a less crystaline complex when AZT was ecapsulated in the amorphous MUC and PEC based SMMs (Mishra et al, 2008;Santos et al, 2003, Shaikh et al, 2009. …”
Section: Thermogravimetric Analysis Of Azt Loaded Smms and Their Natimentioning
confidence: 70%
See 1 more Smart Citation
“…In vitro results have shown that pectin has good biocompatibility and is osteogenic (Kokkonen et al, 2008;Mishra et al, 2008). Despite the fact that pectin possesses the potential to be a biocompatible cross-linker, literature on the characterizations of pectin-cross-linked tissue engineered scaffolds as drug delivery carriers is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…This calcium cross-linking of pectins leads to extensive hydration [19][20][21][22]. Pectin gelling properties achieved a growing interest from scientific audience due to the possibility of obtaining an in situ biocompatible gelling system, for bone tissue engineering [23][24][25], injectable cell delivery system [26] and drug delivery system [27,28].…”
Section: Pectinsmentioning
confidence: 99%